Determination of Mass Transfer Coefficient for Copper Electrodeposition by Limiting Current Technique. - Ibrahim, Marwa H.; Najim, Sarmad T. (Al-Nahrain Journal for Engineering Sciences, 2017)
An experimental study was conducted to investigate the mass transport behavior for electrochemical reduction of copper in the presence of 0.5M H2SO4 as supporting electrolyte by limiting current technique (LCT). The experiments were carried out via rotating cylinder electrode made of copper as cathode. The effects of various operating conditions: rotation rates 100, 200, 300, 400, and 500rpm, electrolyte temperatures 30, 45, and 60?, and cupric ions concentration 250, 500, and 750 ppm on mass transfer rate were studied. It was observed that mass transfer coefficient based mainly on rotation rates, then temperature and finally cupric ions concentration. The electrodeposition of cupric ions was proved to be a mass control. The mass transfer coefficient for rotating cylinder electrode was correlated with the aid of dimensionless groups as follows:Sh = 0.236 Re0.664 Sc0.356And the above correlation is a good agreement with eisenberg equation.